A checklist of the hoverflies (Diptera, Syrphidae) of Armenia - Grigoryan, Nonna; Romig, Thomas; Karagyan, Gayane; Ghrejyan, Tigran; Kalashian, Mark; Mochizuki, Ko (Zootaxa, 2026)
We present a checklist of the hoverflies (Diptera, Syrphidae) of Armenia. The checklist includes 263 species of hoverflies from current or historic collections, which were seen and identified by the authors, or which were explicitly reported from the territory of Armenia in previous publications. Among these, 38 species are reported from Armenia for the first time. The most species-rich genera of the country’s fauna are Cheilosia Meigen, 1822 (44 spp.), Merodon Meigen, 1803 (24 spp.), Eumerus Meigen, 1822 (22 spp.) and Chrysotoxum Meigen, 1803 (17 spp.). In view of the biogeographical position and the diverse topography of Armenia, the species number is suggestive of underreporting. The principal aim of this updated list is the compilation of data from highly scattered sources and their presentation in accessible form, to encourage the further study of syrphid taxonomy and diversity in the region.